Comparative genomics analysis of the MYB gene family in barley: preliminary insights into evolution and biological function in Blue Qingke - Li, Hongyan; Yao, Youhua; Li, Xin; Cui, Yongmei; An, Likun; Ding, Baojun; Yao, Xiaohua; Wu, Kunlun (PeerJ, 2024)
Background The Myeloblastosis related (MYB) family is one of the most widely distributed transcription factor families in plants and plays a significant role in plant growth and development, hormone signal transduction, and stress response. There are many reports on MYB family species, but the research on Qingke is still limited. Methods This study used comparative genomics methods to analyze gene and protein structure, protein physicochemical properties, chromosome localization, and evolution. A bioinformatics approach was used to systematically analyze the HvMYB gene family. At the milk stage, soft dough stage, and mature stage, White and Blue Qingke grains were selected for RNA sequencing (RNA-seq), among which two proteins interacted (HvMYB and HvMYC). The expression of this gene family was analyzed through RNA-seq, and the expression levels of HvMYB and HvMYC in the grains of two different color varieties were analyzed by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Finally, the interaction between HvMYB and HvMYC was verified by bimolecular fluorescence complementation (BiFC) experiments. Results A total of 92 Qingke HvMYB genes were identified and analyzed, and 92 HvMYB proteins were classified into five categories. Cis-acting elements associated with abscisic acid response, light response, and methyl jasmonate (MeJA) response were found in the promoter regions of most MYB genes. Using qRT-PCR combined with RNA-seq analysis showed that MYB gene was highly expressed in the soft dough stage and was varietal specific. Subcellular localization indicated that HvMYB was located in the nucleus and cell membrane, HvMYC was located in the nucleus, cell membrane, and cytoplasm. Through BiFC analysis, it has been proven that HvMYB in the MYB family and HvMYC in the basic helix–loop–helix (bHLH) family can interact. This study provides a preliminary theoretical basis for understanding the function and role of the Qingke MYB gene family and provides a reference for the molecular mechanism of Qingke gene evolution.
Keywords: Qingke; MYB family; Anthocyanin; Gene expression